Raittiutta runoissa I-II: Raittiuskokouksissa lausuttavaksi ja kotona luettavaksi - Tamminen, Em., 1852-1946; Hellman, Juho (Salt Lake City, UT : Project Gutenberg, 2011)
"Raittiutta runoissa I-II: Raittiuskokouksissa lausuttavaksi ja kotona luettavaksi" is a collection of poems written in the late 19th century. This work, attributed to authors Em. Tamminen (Part I) and Juho Hellman (Part II), focuses on themes of sobriety and the dangers of alcohol, reflecting a broader social movement for temperance during that time. The collection includes original poems, adaptations, translations, and humorous verses aimed at promoting the principles of teetotalism and raising awareness about the negative effects of alcoholism. The opening of the collection features several poems that highlight the struggles against alcohol, invoking strong imagery of battles against the evils of drunkenness. The authors employ passionate language to rally the reader's sentiments, suggesting that the fight against alcohol is a moral and spiritual crusade. In these initial verses, the tone oscillates between fervent denunciations of drinking and the promise of redemption through sobriety, appealing to both the heart and conscience of the audience. (This is an automatically generated summary.)
Release date is 2011-08-09
Produced by Tapio Riikonen
Keywords: Temperance -- Poetry